ANALISIS PENGARUH IDLE TIME DAN NOT OPERATION TIME TERHADAP PRODUKTIVITAS BONGKAR MUAT (BSH) PADA DERMAGA INTERNASIONAL PERUSAHAAN BONGKAR MUAT DI SURABAYA - Alfina Cintika Putri; Fitri Hardiyanti; Alfred Bawole (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
The productivity of container loading and unloading at the dock is influenced by the utilization of time, including both idle time and not operation time. The productivity of a dock is also a benchmark for determining the success of loading and unloading activities. High idle time and not operation time have disrupted the productive activities of the dock. The high ineffective time results in many ships having to dock longer than planned. This study aims to analyze the impact of idle time and not operation time on loading and unloading productivity (BSH), specifically at the international dock of a stevedoring company in Surabaya. This research uses a quantitative method with data from December 2023. The data collection method used is documentation of internal company data from the stevedoring company in Surabaya. The sampling method used is saturated sampling with a total sample of 85 ships. The analysis methods used in this research are descriptive analysis and multiple linear regression analysis. The results of this study show that the idle time variable has a positive and significant impact on loading and unloading productivity (BSH). In contrast, the not operation time variable does not have a substantial effect on loading and unloading productivity (BSH). Additionally, idle time and not operation time have a simultaneous significant impact on loading and unloading productivity (BSH)